Sprejemanje tehnologij blagostanja med medicinskimi sestrami - Hvalič Touzery, Simona (Informatica Medica Slovenica, 2023)
Welfare technologies, which encompass a wide range of technologies used to maintain or improve individuals’ functioning, safety, participation or independence, are becoming inevitable for health care and long-term care. These technologies are also impacting nursing practice. However, little is known about their acceptance among nurses who work with older adults outside of the clinical setting. The goal of this five-stage scoping review was to address this knowledge gap. A comprehensive search of seven bibliographic databases (MEDLINE, CINAHL with full text, PubMED, Scopus, Proquest Social Sciences Database, APA PsycArticles, and SocINDEX with full text) and grey literature was conducted in December 2022. Based on the inclusion and exclusion criteria, 27 articles were selected. The content-based analysis conducted using ATLAS.ti 9 software identified five categories of acceptance factors: individual, organizational, patient-related and technological factors, and social influence. Notably, patient-centeredness was found to be represented in all five categories. In the future, the factors that influence nurses' acceptance of new technologies should be researched before the technologies are put into use.
Keywords: assistive technology; Medicinska tehnologija; Medicinske sestre; pametne tehnologije; podporna tehnologija; Robotika v medicini; scoping review; smart technologies; sprejemanje tehnologij; študija obsega; technology acceptance; Telemedicina; Zdravstvena nega